РАСЧЕТ МАГНИТНОГО ПОТОКА В ОКНЕ U-ОБРАЗНОГО ЭЛЕКТРОМАГНИТА - Загирняк, М.В. (Інститут електродинаміки НАН України, Київ, 2013)
To develop control circuits for direct current electromagnets (magnetic separators, lifting electromagnets, actuators) it is necessary to calculate their windings inductances. Estimation of inductance requires determination of winding flux linkage. In the present paper the mentioned problem is solved analytically referring to U-shaped electromagnet with a rectangular window space where two energized coils are located. In this case the assigned problem is to determine the inter-coil gap influence on the value of vector potential and, correspondingly, the scattered-flux linkage (inductance). As a result, distribution of vector magnetic potential has been determined for U-shaped electromagnet window space by Rogovskii’s method. An analytical expression for winding scattered-flux linkage (two coils) and its inductance has been obtained. Curves determining winding scatter specific inductance are shown for the considered electromagnet. An inductance component conditioned by the gap between two coils has been singled out and presented by an algebraic expression. Calculations of the given scatter inductances in electric systems of industrial suspended guard magnets proved the necessity for taking inter-coil gap into consideration. References 10, table 1, figures 3.